Impaired heme oxygenase‐1 induction in the gastric antrum induces disruption of the interstitial cells of Cajal network in a rat model of streptozotocin‐induced diabetes. Issue 7 (27th March 2013) - Mogami, S.; Suzuki, H.; Tsugawa, H.; Fukuhara, S.; Hibi, T.
Abstract: Background: Streptozotocin (STZ) is known to induce type I diabetes and the loss of the interstitial cells of Cajal (ICC). However, the regulation of heme oxygenase‐1 (HO‐1) expression, which is reported to protect ICC, has not yet been elucidated in this model. The aim of this study was to investigate the alterations of HO‐1 expression and clarify the mechanism of ICC loss in the stomach using the rat model of STZ‐induced diabetes. Methods: Streptozotocin (65 mg kg −1 ) was intraperitoneally administered to 8‐week‐old female Wistar rats. Cobalt protoporphyrin (CoPP), an HO‐1 inducer, was administered subcutaneously once a week after the STZ injection. The expressions of HO‐1 and the receptor tyrosine kinase c‐Kit (a marker for ICC) proteins were investigated by western blot analysis and immunofluorescence staining. Key Results: Expression of c‐Kit, particularly in the gastric antrum, was significantly decreased at 8 weeks, not at 1 week, compared to those of the control group. Significantly increased induction of HO‐1 expression, especially in the gastric corpus but not in the antrum, was observed in the STZ group at 8 weeks after the STZ injection relative to control. CoPP administration significantly up‐regulated HO‐1 expression in the STZ diabetic group and significantly restored the previously reduced ICC in the gastric antrum. Conclusions & Inferences: Up‐regulation of HO‐1 expression in the STZ diabetic model was limited to the gastric corpus and impaired up‐regulation of HO‐1 expression in the gastric antrum likely induced the disruption of the ICC network.